PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR PKN DI SMP PGRI PEKANBARU - Saraswati, Shinta; Erlinda, Sri; ', Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was a backdrop of unrest in the process of civic education, more teachers tend to use conventional learning, the teacher is more likely to be less creative in the process of civic education, the process of civic education only contains lectures boring, feeding (spoon feending), not fun but scary, students are not invited to take advantage of its potential, and the methods used often varied. So that student learning outcomes are still many under the KKM, hence the need for a learning method for improving student learning outcomes. His formulation of how the influence of jigsaw cooperative learning model for learning outcomes Civics In SMP PGRI Pekanbaru. The aim of research to determine student learning outcomes after using model-type koopertif jigsaw on the subjects of Civics in SMP PGRI municipality Pekanbaru. The study population of students of class VII SMP PGRI Pekanbaru, Pekanbaru municipality, school year 2015-2016, amounting to 150 students. Samples class VIIA and VIIB SMP PGRI municipality Pekanbaru, divided into the control class numbered 27 students and class totaled 25 students experiment. Data collection techniques were used that observation, questionnaires, interviews and documentation. Data were analyzed using student activities, the activities of teachers and learning outcomes. The findings in this study were 1) the activity of the teacher of the whole meeting the average value of the whole meeting 78.89 including a perfect category, 2) student activity overall average of 85.67 meeting very high category. 3) The learning outcomes of student learning outcomes that the value of t at 2.75, then confirmed with t table at a significance level of 5% = 0.05, df = n1 + n2 - 2, the obtained value of t table is 1.68, thitung> ttabel or 2.75> 1.68. In this study, the hypothesis was accepted because thitung greater than ttabel or Ho rejected and Ha accepted.Keywords: TipeJigsaw Cooperative Learning, Learning Outcomes